Effect of Combination of Manure and Mycorrhiza on Fruit Quality and Storability of Tomato in Organic Farming Lembang - Soelistianto, Farida Arinie; Priyana, Yana; Bunyamin, Ilham Akbar (West Science Interdisciplinary Studies, 2025)
This study investigates the effect of a combination of manure and mycorrhiza on the quality and storability of tomatoes from the perspective of organic farmers in Lembang, utilizing a quantitative analysis with 140 samples. Data were collected using a Likert scale (1-5), and the analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that manure positively impacts fruit quality and storability, with a stronger effect on storability. Mycorrhiza had a more significant effect on fruit quality and also positively influenced storability. The study found that mycorrhiza is the more dominant factor in improving fruit quality, while manure plays a more significant role in enhancing storability. The findings provide important insights for organic farming practices in Lembang, suggesting that a combination of manure and mycorrhiza can effectively enhance both the quality and shelf life of tomatoes.
Keywords: Manure; Mycorrhiza; Tomato Quality; Storability; Organic Farming